Pengaruh Literasi Keuangan, Inklusi Keuangan, Gaya Hidup, Pengendalian Diri, dan Perilaku Konsumtif Terhadap Perilaku Pengelolaan Keuangan Pada Penggemar K-Pop - Siti Asiyah; Setiawati, Erma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of financial literacy, financial inclusion, lifestyle, and self-control on financial management behavior, with a particular focus on K-pop fans in Java Island. The research employs a quantitative approach using primary data collected through questionnaires. The population of this study consists of K-pop fans, and a total of 217 respondents were obtained as samples through Google Forms distributed via social media platforms. The data were analyzed using SPSS 25 with several analytical methods including data quality tests, classical assumption tests, and multiple linear regression analysis. The results indicate that financial literacy and self-control have a significant influence on the financial management behavior of K-pop fans. Meanwhile, financial inclusion, lifestyle, and consumptive behavior do not show a significant effect on financial management behavior.